Fractals and multifractals in ecology and aquatic science - Seuront, Laurent (CRC Press/Taylor & Francis, 2010)
"Ecologists sometimes have a less-than-rigorous background in quantitative methods, yet research within this broad field is becoming increasingly mathematical. Written in a step-by-step fashion, Fractals and Multifractals in Ecology and Aquatic Science provides scientists with a basic understanding of fractals and multifractals and the techniques for utilizing them when analyzing ecological phenomenon. With illustrations, tables, and graphs on virtually every page - several in color - this book is a comprehensive source of state-of-the-art ecological scaling and multiscaling methods at temporal and spatial scales, respectfully ranging from seconds to months and from millimeters to thousands of kilometers. It illustrates most of the data analysis techniques with real case studies often based on original findings. It also incorporates descriptions of current and new numerical techniques to analyze and deepen understanding of ecological situations and their solutions."--Publisher's description.
Keywords: Biomathematics.; Mathematics in nature.; Ecology -- Mathematics.; Aquatic sciences -- Mathematics.; Fractals.; Multifractals.; elektronické knihy; electronic books